Correlation of post mortem LODOX digital radiological images with histopathological findings at autopsy : a prospective autopsy study at the Tygerberg Forensic Pathology Service Facility - Quarrie, Karisha Claudia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2015.